Pengaruh Variasi Pemadatan Terhadap Karakteristik Marshall dengan Menggunakan Wood Ash Sebagai Filler pada Campuran Laston - Alamsyah, Alik Ansyori; Darmawan, Azhar Adi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Indonesia's population is increasing exponentially, causing increased mobility. Therefore, it is necessary to increase the quantity and quality of roads to meet community needs. In Indonesia, hot mix asphalt, also known as hot mix, is the most common type of mix. Asphalt Concrete (AC) consists of asphalt as an adhesive, coarse aggregate and fine aggregate, and filler as a filling material, according to the 2010 BM specifications. All materials used in this research refer to the general specifications issued by the Directorate General of Highways in 2010 Revision 3, and the Marshall test will be carried out by replacing the Portland cement filler with Wood Ash in the Laston mixture. The asphalt used has a penetration of 60/70 and is used with compaction variations of 40, 50, 60 and 80 impacts. The research using wood asphalt as a filler showed a Marshall stability of 840.72 kg, a Marshall coefficient of 3.49 kN/mm, a film thickness of 6.64 Î¼m, and an air mist volume of 4.59%.